2019
DOI: 10.1038/s41598-019-49133-w
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Glucocorticoid Receptor and Serum Corticosterone Expression in a Rodent Model of Noise-induced Hearing Loss: Comparison of Timing of Dexamethasone Administration

Abstract: Glucocorticoid (GC) is a steroid hormone secreted from the adrenal cortex in response to stress, which acts by binding to cytoplasmic glucocorticoid receptors (GRs). Dexamethasone (DEX) is a synthetic GC exhibiting immunosuppressive effects in both human and rodent models of hearing loss. While clinical evidence has shown the effectiveness of DEX for treatment of various inner ear diseases, its mechanisms of action and the optimal timing of treatment are not well understood. In the present study, intergroup co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Samples from mice aged 2 and 20 months were collected. Cochlear tissues were obtained to localize inner and outer hair cells and neuronal fibers as previously described [20,21]. Briefly, tissues were fixed in 4% paraformaldehyde in phosphate-buffered saline (PBS) for 1 h at room temperature to remove the cochlear bony walls and lateral wall tissues and separated individual cochlear turns.…”
Section: Tissue Preparation and Immunofluorescencementioning
confidence: 99%
“…Samples from mice aged 2 and 20 months were collected. Cochlear tissues were obtained to localize inner and outer hair cells and neuronal fibers as previously described [20,21]. Briefly, tissues were fixed in 4% paraformaldehyde in phosphate-buffered saline (PBS) for 1 h at room temperature to remove the cochlear bony walls and lateral wall tissues and separated individual cochlear turns.…”
Section: Tissue Preparation and Immunofluorescencementioning
confidence: 99%
“…Notably, in rodents, glucocorticoid receptors are found throughout the cochlea, particularly in the stria vascularis, inner hair cells, outer hair cells, and spiral ligament of the cochlea and cochlear nerve. In humans, the highest concentration of receptors is found on the spiral ligament [32][33][34]. Moreover, it has been demonstrated that the intratympanic application of dexamethasone supports cochlear homeostasis under stress conditions such as noise-trauma in multiple animal models [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In the study presented herein, a genomic mechanism of action could be expected due to the applied dexamethasone concentrations ranging from 5 pg to 5 fg. In humans, the highest concentration of glucocorticoid receptors required for the action of dexamethasone are mainly located in the spiral ligament (Rarey and Curtis 1996 ; Lee et al 2019 ) and increase from basal to apical in type I, II and V fibrocytes (Kil and Kalinec 2013 ). In addition, glucocorticoid receptors are also located in inner and outer hair cells as well as in the auditory nerve (Lee et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the highest concentration of glucocorticoid receptors required for the action of dexamethasone are mainly located in the spiral ligament (Rarey and Curtis 1996 ; Lee et al 2019 ) and increase from basal to apical in type I, II and V fibrocytes (Kil and Kalinec 2013 ). In addition, glucocorticoid receptors are also located in inner and outer hair cells as well as in the auditory nerve (Lee et al 2019 ). Understanding the exact mode of action would give us important information about the time frame before or after electrical stimulation in which treatment should have been initiated.…”
Section: Discussionmentioning
confidence: 99%